Anti-Infective Effect of Adhesive Probiotic Lactobacillus in Fish is Correlated With Their Spatial Distribution in the Intestinal Tissue. Issue 1 (December 2017) - He, Suxu; Ran, Chao; Qin, Chubin; Li, Shuning; Zhang, Hongling; Vos, Willem; Ringø, Einar; Zhou, Zhigang
Abstracr In this study, we tested the distribution of 49Lactobacillus strains in the mucus and mucosa of the intestine tissue of zebrafish. We observed a progressive change in the spatial distribution ofLactobacillus strains, and suggested a division of the strains into three classes: mucus type (>70% in mucus), mucosa type (>70% in mucosa) and hybrid type (others). The hybrid type strains were more efficient in protection of zebrafish againstAeromonas hydrophila infection. Three strains representing different distribution types (JCM1149, CGMCC1.2028, and JCM 20300) were selected. The mucosa type strain JCM1149 induced higher intestinal expression of inflammatory cytokines andHsp70 than the other strains. Furthermore, we usedL. rhamnosus GG and its mutant (PB22) lacking SpaCBA pili to investigate the influence of pili on spatial distribution. LGG showed a mucosa type distribution, while PB22 revealed a hybrid distribution and the disease protection was accordingly improved. The different protection ability between LGG and PB22 did not involve the intestinal microbiota, however, LGG induced injury to the mucosa of zebrafish. Collectively, the disease protection activity ofLactobacillus in zebrafish is correlated with their spatial distribution in the intestinal tissue, with strains showing a balanced distribution (hybrid type) more efficient in protection.